SHEATHLIKE METASOMATIC GARNET CRYSTALS FROM THE MAKSYUTOVO METAMORPHIC COMPLEX, THE SOUTHERN URALS - Zhdanov V.V.; Glikin A.E. (My University, 2006)
The Maksyutovo Complex is located in the southern Urals as a near-meridional belt 180 km long and 12–16 km wide. Eclogites and products of their metasomatic alteration (schists) are widespread in this complex. The alteration begins from the alkaline sodic metasomatism that fostered replacement of eclogites with glaucophane schists. Sodic metasomatism gave way to potassic metasomatism. Both the relict eclogites and glaucophane schists were replaced with phengite schists.
Keywords: Maksyutovo Complex; southern Urals